(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify" the effect of (Shor) strategy on the habits of mind of fourth-grade students in science in biology". To achieve the research objective, the following null hypothesis was formulated There is no statistically significant difference at the level (0.05) between the average scores of the experimental group students who studied according to the (shor) strategy and the average scores of the control group students who studied according to the (ordinary method) in the Habits of Mind scale. The researcher adopted the experimental design with partial control for the experimental and control groups in the Habits of Mind scale, representing the current research community of all fourth-grade students who study in all public preparatory and secondary day schools for girls affiliated to the General Directorate of Anbar Education, Haditha Judiciary Center for the academic year ( 2021-2022). ), and the research sample amounted to (75) female students, with three divisions (A, B, and C), which numbered (25) students. shor) and Division (C), which represents the control group that studied according to the usual method with (25) students for the experimental and control group, and the experimental and control groups were rewarded in the variables (age calculated in months, previous information for biology, intelligence (Raven), scale Habits of the Mind) and after defining the study material, the study material was identified that was represented by the chapters (first - second - third from page 29 - 36 - chapter five - chapter six) of the book of revival scheduled for the fourth scientific grade Authored by the Iraqi Ministry of Education / Tenth Edition / for the year 2019 AD, the researcher formulated behavioral objectives that amounted to (358) behavioral objectives. The experiment started on Thursday (4/11/2021) on the two research groups (experimental and control), and the experiment ended on Monday (24/1/2022), with a duration of (11) weeks and a number of Lessons (3) for each of the experimental and control groups. The researcher used the statistical program (SPSS), including (t-test for two independent samples, chi-square (Ka2), Pearson’s correlation coefficient, alpha-Cronbach equation). In addition to the Microsoft Office Excel 2016 data processor program In light of this, the results concluded that there was a statistically significant difference in favor of the experimental group in the Habits of Mind scale.